Agresivitas Pajak: Capital Intensity, Corporate Social Responsibility (CSR), Leverage, Dan Ukuran Perusahaan - Aulia Rahma Dien Yulyanti; Mujiyati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The objective of this study is to examine the influence of Capital Intensity (CI), Corporate Social Responsibility (CSR), Leverage Ratio (LEV), and Firm Size on Tax Aggressiveness, using the Effective Tax Rate (ETR) as the measurement. This research focuses on companies in the cyclical sector that are publicly traded on the Indonesia Stock Exchange between 2021 and 2023. The study utilizes secondary data derived from annual reports and sustainability reports sourced from the official website of the Indonesia Stock Exchange (www.idx.co.id) as well as the respective companies' websites. The methodology employed in this research involves panel regression analysis, conducted using SPSS software. The findings indicate that Corporate Social Responsibility (CSR) and Leverage (LEV) do not have a significant impact on tax aggressiveness, whereas Capital Intensity (CI) and Firm Size (SIZE) do influence Tax Aggressiveness.